A Midlatitude HF Propagation Experiment Over New Mexico. Issue 3 (27th March 2019) - Munton, David; Rainwater, D.; Gaussiran, T.; Calfas, R.; Reay, M.; Schofield, J.; Fleischmann, A.
Abstract: We describe a midlatitude ionospheric measurement experiment conducted 19–27 January 2014 at White Sands Missile Range, New Mexico, United States. This experiment was one of a series of experiments conducted under the IARPA high‐frequency Geo program. The objective was to develop a data set to be used by data assimilation studies focused on modeling of the bottomside of ionosphere and high‐frequency signal propagation. We outline the specific objectives of the experiment and the experimental configuration and describe the transmit sites and antenna array that allowed us to estimate angles‐of‐arrival for both O‐ and X‐mode signals. We provide a detailed example from 22 January 2014. This period shows the variations characteristic of medium‐scale traveling ionospheric disturbances. We use the data from this period to estimate the resolution of our angle‐of‐arrival measurements to be about 0.1°. Key Points: We conducted an HF propagation experiment to be used with data assimilation studies as part of the IARPA HFGeo program Measurements utilized an antenna array to obtain angles‐of‐arrival for both O and X modes Medium‐scale traveling ionospheric disturbances were seen in measurements over most of the experiment